A new lachesilla from the bolivian chiquitania, in species group riegeli (PSOCODEA: PSOCOMORPHA: LACHESILLIDAE) - García Aldrete, Alfonso N. (Instituto de Ecología, A.C., 2017)
ABSTRACT. A species of Lachesilla in species group Riegeli, fromthe Bolivian Chiquitania, is here described and illustrated. It is the first species in that group to be recorded in Bolivia. It is close to L. paulista García Aldrete, from Argentina and Brazil. An identification key to the males of the species in group Riegeli is included.